Estimates of gene action in bitter gourd (Momordica charantia) - Dey, SS; Behera, TK Behera; Munshi, AD Munshi; Bhatia, R Bhatia (Vegetable Science, 2011)
Bitter gounrd (Momordica charantia L.) is a member of the family cucurbitaceae. India is endowed with a wide range of diversity in this crop, so there is a vast opportunity for genetic improvement.